Evaluation of Antibiotic Sensitivity Pattern and Plasmid Isolation of Klebsiella Pneumoniae Isolates from Clinical Specimens in Sylhet City, Bangladesh (Journal of Scientific Research, 2017)
Klebsiella pneumoniae is recognized as an emerging opportunistic bacterial pathogen of clinical relevance for its association with both community acquired and nosocomial infections. Moreover, increased resistance to common antimicrobial agents complicates and limits available therapeutic options. The aim of this study was to investigate an antibiotic sensitivity pattern of K. pneumoniae isolated from clinical samples against commonly used antibiotics and to focus on the associated therapeutic challenges. Presumptive K. pneumoniae isolates were collected from a variety of sources like urine sample, pus, wound swab etc. and further analyzed through standard microbiological methods. Following the identification of 23 bacterium isolates from the collected specimens, an antimicrobial sensitivity test was carried out. The results of this test indicated that the organisms possess diversity of susceptibility profiles towards the drugs tested. A high rate of resistance to the first line antibiotics like Amoxicillin (100%), Vancomycin (90.90%), Erythromycin (83.33%), and Cotrimoxazole (83.33%), designates a critical therapeutic challenge. However, inspite of a moderate sensitivity to the Gentamicin (43.5%), increased number of intermediate sensitivity to the drugs tested clearly point towards the multi-drug resistance of the K. pneumoniae isolates. Plasmid profiling experiment revealed that the size of the isolated plasmids varied in length, ranging from 800-900bp.